Long-term comparison of Charnley and Stanmore design total hip replacements. - Britton, A; Murray, D; Bulstrode, C; McPherson, K; Denham, R (1996)
We reviewed the records of the long-term outcome of 208 Charnley and 982 Stanmore total hip replacements (THR) performed by or under the supervision of one surgeon from 1973 to 1987. The Stanmore implant had a better survival rate before revision at 14 years (86% to 79%, p = 0.004), but the difference only became apparent at ten years. The later Stanmore implants did better than the early ones (97% to 92% at ten years, p = 0.005), the improvement coinciding with the introduction of a new cementing technique using a gun. Most of the Charnley implants were done before most of the Stanmore implants so that the difference between the results may in part be explained by improved methods, but this is not the complete explanation since a difference persisted for implants carried out during the same period of time. We conclude that improved techniques have reduced failure rates substantially. This improvement was much greater than that observed between these two designs of implant. Proof of the difference would require a very large randomised controlled trial over a ten-year period.